Biological chirality - Palyi, Gyula (Collana di studi (Accademia di scienze, lettere e arti (Modena, Italy)) ;, 2019)
Biological Chirality describes this occurrence, its history, and early research around the topic. The work covers analytical methods for observing the phenomenon, providing current techniques and practice and discussing the asymmetric morphology of certain living organisms, such as the position of the heart and liver in humans and the exceptions to biological homochirality seen in D-Amino Acids. In addition, it explores the requirement of enantioselectivity prepared pharmaceuticals to address enantioselectivities biomolecules, a major challenge in today's organic chemistry. Finally, the work considers the possible origin of biological homochirality, as well as the outlook for future research in this area.